Glis1 and oxaloacetate in nucleus pulposus stromal cell somatic reprogramming and survival - Lufkin, Leon; Samanta, Ankita; Baker, DeVaun; Lufkin, Sina; Schulze, JesslynHope; Ellis, Benjamin; Rose, Jillian; Lufkin, Thomas; Kraus, Petra (Frontiers in Molecular Biosciences, 2022)
Regenerative medicine aims to repair degenerate tissue through cell refurbishment with minimally invasive procedures. Adipose tissue (FAT) derived stem or stromal cells are a convenient autologous choice for many regenerative cell therapy approaches. The intervertebral disc (IVD) is a suitable target. Comprised of an inner nucleus pulposus (NP) and outer annulus fibrosus (AF), degeneration of the IVD through trauma or aging presents a substantial socio-economic burden worldwide. The avascular nature of the mature NP forces cells to reside in a unique environment with increased lactate levels, conditions that pose a challenge to cell-based therapies. We assessed adipose and IVD tissue derived stromal cells through in vitro transcriptome analysis and show in 2D and 3D culture that adipose stromal cells can face the challenge but undergo extensive somatic reprogramming under degenerate NP niche conditions and reveal higher immunogenicity and senescence than NP cells, which developed a survival mechanism based on lactate metabolism.